PENGARUH TUMPANGSARI TANAMAN SAWI (Brassica juncea Linn.) DAN TANAMAN TOMAT (Solanum lycopersicum Linn.) TERHADAP SERANGAN Plutella xylostella Linn. (Lepidoptera: Plutellidae) - Simarmata, Goklas; Pasaru, Flora; Nasir, Burhanuddin (AGROTEKBIS, 2017)
Implementation of the intercropping of tomato with mustard plants in Central Sulawesi Palu valley region in particular in Palu Valley is very little conducted by farmers. Habits of farmers especially in the area of Central Sulawesi in controlling pests of horticultural crops are still relying on the use of chemical insecticides with relatively high doses concentration. This study aims to determine the effect of intercropping of tomato and mustard plants on the attack of Plutella xylostella L. This research is compiled using a randomized block design with 4 treatments were repeated 3 times. Variables measured the population density of P. xylostella L, the intensity of the attacks, and the production of mustard. The results showed intercropping of tomato plants can significantly affect suppress the population, the intensity of P. xylostella L and mustard production. The highest population is in the control treatment with 1.80 tail and lowest population for the treatment of mustard planted on the sidelines of the tomato crop in the direction from east to west by 0 tail. The intensity of the attacks is highest in the control treatment of 62,80 % and the lowest for the treatment of mustard planted on the sidelines of the tomato crop in the direction from east to west. The high production was 3.82 ton/ha in treatment of mustard surrounded by tomato plants and the lowest production found on control treatments contained 1.67 ton/ha.Â Keywords : Intercropping, Mustard, Plutella xylostella.